Molecular weight effect on polymer dissolution: a steady state fluorescence study - Pekcan, Önder; Uğur, Şaziye (Elsevier BV, 2002)
Abstract In situ steady state fluorescence (SSF) technique was used to study the dissolution of disc-shaped polymer glasses in various molecular weights, M W . The glass discs were formed by free-radical polymerization of methyl methacrylate (MMA). Pyrene (P) was introduced during polymerization as a fluorescence probe to monitor the dissolution process in chloroform. Desorption of poly(methyl methacrylate) (PMMA) chains from discs were monitored simultaneously by observing the change of P fluorescence intensity, I . Diffusion model with a moving boundary was employed to quantify the fluorescence data observed from dissolving PMMA discs made at various molecular weights. It is observed that desorption coefficient, D decreased by increasing molecular weight, M W by obeying D ≈ M −1 law.